Utilisation of ANC services before and after the COVID-19 pandemic in selected resource-poor blocks of India: role of community health workers in Swabhimaan programme area - Preeti Dhillon; Sayeed Unisa; Ajay Gupta; Abhishek Saraswat; Sulaiman KM; Sarang Pedgaonkar (BMC, 2023)
Abstract Introduction COVID-19 has disrupted maternal and child health services. Community Health Workers (CHWs) supported the women by visiting pregnant women's homes and providing the MCH services as required. This study attempts to understand the role of CHW and its impact on the Ante-Natal Care (ANC) services pre-pandemic and post-Pandemic in the poor resource setting. Methods The Swabhimaan programme interventions were carried out in the selected blocks in the Indian States of Bihar, Odisha and Chhattisgarh with the objective to improve the nutritional status of mothers, pregnant women and adolescents living in resource-poor blocks of three selected states during 2016-2022. Cross-sectional surveys, namely pre-pandemic (2018-19) and post-pandemic (2021-22) of pregnant and mothers of under two children, utilised to fulfil the objectives of this study. These surveys are part of Swabhimaan evaluation, a community-based non-randomised controlled study. Results The ANC services received by women have increased over time from 2015 to 2022. Our findings confirm that the ground-level community and health systems were active during the pandemic, and the results show significant improvement. Additionally, the women supported by the CHW have substantially improved pregnancy registration, first ANC, Tetanus injection, consumption of Iron Folic Acid, Calcium and deworming tablets than those who did not. Propesnsity Score Matching analysis shows that the average treatment effect on the various ANC services of having the support of CHW is significant. Conclusion This study shows the vital role of CHWs in utilising various Maternal and Child Health services. Better linkage and networking of the CHWs with the community will ensure health service delivery regularly and in an emergency like a pandemic and develop resilience.